Identified charged particles in quark and gluon jets - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (2000)
A sample of 2.2 million hadronic Z decays, selected from the data recorded by the DELPHI detector at LEP during 1994-1995 was used for an improved measurement of inclusive distributions of π+ K+ and p and their antiparticles in gluon and quark jets. The production spectra of the individual identified particles were found to be softer in gluon jets compared to quark jets, with a higher multiplicity in gluon jets as observed for inclusive charged particles. A significant proton enhancement in gluon jets is observed indicating that baryon production proceeds directly from colour objects. The maxima, £*, of the ξ -distributions for kaons in gluon and quark jets are observed to be different.